Mobile messaging and smartphone apps for patient communication and engagement in spine surgery - Goz, Vadim; Spiker, William Ryan; Brodke, Darrel (Annals of Translational Medicine; Vol 7, Supplement 5 (September 10, 2019): Annals of Translational Medicine (Focus on: “Current Trends and Advancements in Spine Surgery”), 2019)
Mobile health (mHealth) applications are rapidly becoming increasingly available to patients. These interventions utilize simple mobile messaging (SMS) and software applications on mobile devices for a variety of purposes. In the surgical population mHealth applications have shown promise in increasing medication and protocol adherence, monitoring patients after surgery, and helping modify behaviors associated with poor surgical outcomes. There is a paucity of spine specific applications at this time. Further development and study of efficacy of spine specific mHealth applications is needed.